(untitled) (Plant Tissue Culture and Biotechnology, 2019)
The experiment was conducted to assess five tropical strawberry genotypes at phenotypic and molecular level. Among the five strawberry genotypes (BARI Strawberry 1, BARI Strawberry 2, BARI Strawberry 3, FA 005 and Festival), BARI Strawberry 2 was found to be the best in respect of fruit per plant (32.42), fruit yield per plant (594.73 gm) and yield per hectare (19.39 ton). Ten SSR primers were initially screened for molecular characterization and finally MFv104, ARSFL-10 and ARSFL-15 markers were selected for the analysis. EMFv104 and ARSFL-15 produced the maximum number of polymorphic alleles (4) while ARSFL-10 produced three polymorphic alleles. The major allele frequency at each locus ranged from 0.4 (EMFv104) to 0.6 (ARSFL-10). The PIC values varied from 0.4992 on ARSFL-10 to 0.672 on EMFv104. The gene diversity ranged from 0.56 (ARSFL-10) to 0.72 (EMFv104 and ARSFL-15). BARI Strawberry 1 and Festival were the closest genotypes with the lowest genetic dissimilarity value of 0.16667. EMFv104 and ARSFL-15 can be used as polymorphic markers for assessing genetic diversity of different strawberry genotypes.